The Development of Diorama Media as a Covid-19 Educational Means in 2021 - Rohmatul Laili, Intan; Asmarani, Ratih (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
The development of this diorama media was motivated by several gaps, including: 1) students had never received interesting education about covid-19, 2) diorama media did not teach students to understand covid-19, 3) general students did not understand about covid-19 yet, so the development of three dimensions model media and their implementation was carried out at Mundusewu Primary School 3 Jombang. Based on the problems that have been described, this development aims to determine the process of developing diorama media for fourth grade students at Mundusewu Primary School 3 Jombang and understand the implementation of it. The research method used is research and development, modified by the Sugiyono and Borg and Gall models as needed. The assessment of the diorama media is carried out by material experts, media experts, users or educators and fourth grade students. The results of the research showed the percentage of media experts was 79.41%. In stage I, the percentange of material experts was 86.11%. Then, in stage 2 the percentange of material expert became 88.88%. In addition, the results of users or educators are 94.4%. The product test resulted 6 students were in the category of very attractive with a percentage of 92.59%, and the usability test for 15 students reach a percentage of 98.45% which is included in the very attractive category. Based on the results of data analysis in general, it can be concluded that the diorama media is feasible to be developed as a learning media.